Influenza Virus-Induced Type I Interferon Leads to Polyclonal B-Cell Activation but Does Not Break Down B-Cell Tolerance - Woods, Anne (American Society for Microbiology (ASM), 2007)
The link between infection and autoimmunity is not yet well understood. This study was designed to evaluate if an acute viral infection known to induce type I interferon production, like influenza, can by itself be responsible for the breakdown of immune tolerance and for autoimmunity. We first tested the effects of influenza virus on B cells in vitro. We then infected different transgenic mice expressing human rheumatoid factors (RF) in the absence or in the constitutive presence of the autoantigen (human immunoglobulin G [IgG]) and young lupus-prone mice [(NZB × NZW)F(1)] with influenza virus and looked for B-cell activation. In vitro, the virus induces B-cell activation through type I interferon production by non-B cells but does not directly stimulate purified B cells. In vivo, both RF and non-RF B cells were activated in an autoantigen-independent manner. This activation was abortive since IgM and IgM-RF production levels were not increased in infected mice compared to uninfected controls, whether or not anti-influenza virus human IgG was detected and even after viral rechallenge. As in RF transgenic mice, acute viral infection of (NZB × NZW)F(1) mice induced only an abortive activation of B cells and no increase in autoantibody production compared to uninfected animals. Taken together, these experiments show that virus-induced acute type I interferon production is not able by itself to break down B-cell tolerance in both normal and autoimmune genetic backgrounds.